Tailored manganese oxide and nickel sulfide composites with MWCNTs as platinum-free electrodes for solar energy conversion - Diana Suleimenova; Yerbolat Tashenov; Ayagoz Ibrayeva; Robert J. O’Reilly; Bakhytzhan Baptayev; Mannix P. Balanay (Scientific Reports)
Abstract This study investigates the electrocatalytic performance of binary MnO/NiS and ternary MWCNT@MnO/NiS composites as platinum (Pt) free counter electrodes (CEs) for triiodide reduction in dye sensitized solar cells (DSSCs). The MnO and NiS components form mixed phase structures, MnO/Mn₃O₄ and NiS/Ni₃S₄, respectively, while multiwalled carbon nanotubes (MWCNTs) function as a conductive scaffold to enhance charge transport. The composites were synthesized via a solvothermal method and thoroughly characterized using a combination of structural and electrochemical techniques. Both MnO/NiS and MWCNT@MnO/NiS electrodes demonstrated significantly lower charge transfer resistance than the conventional Pt CE, indicating superior catalytic activity. When integrated into DSSCs, the MnO/NiS and MWCNT@MnO/NiS electrodes achieved power conversion efficiencies (PCEs) of 8.66% and 9.29%, respectively, surpassing that of the Pt based device (8.54%) under identical testing conditions. The enhanced performance is attributed to the synergistic effects between the redox active mixed metal phases and the high conductivity and surface area of MWCNTs. Additionally, the devices exhibited excellent long term operational stability, underscoring the potential of these composite materials as cost effective and durable alternatives to noble metal CEs in next generation solar energy systems.